Pengembangan Model Kesiapan UMKM di Era Revolusi Industri 4.0 - Sari, Rianita Puspa; Santoso, Deri Teguh (Jurnal Media Teknik dan Sistem Industri, 2019)
Abstract— Entering the era of the Industrial Revolution 4.0 impacted MSMEs as economic sector builders. Industry 4.0 refers to the concept of internet of things use, as well as smart and cloud based manufacturing. The change in the industrial revolution was faced with the Making Indonesia 4.0 with one of its priorities to empower MSMEs. Constraints of MSME actors from capital, managerial skills, to the use of technology, so that it requires a readiness of MSMEs in the face of Industry 4.0. In this study, UMKM readiness refers to the e-readiness concept to determine readiness in adopting, using and utilizing information technology. The purpose of the research is the development of a model to identify the readiness of MSMEs in Kab. Karawang against industrial revolution 4.0 The research method is descriptive research to develop a research model in identifying the readiness of MSMEs in the era of industrial revolution 4.0, with a random sampling method of 100 respondents. Research results in the form of research model development with survey results stating that many young MSME actors are able to adapt and capture opportunities for current development and market demand, but not following the MSME community are of particular concern so that further approaches are needed in developing the MSME industry in Karawang Regency, so that coaching can be done.Keywords— MSMEs  readiness; Industry 4.0; e-readiness. Abstrak— Memasuki era Revolusi Industri 4.0 berdampak pada UMKM sebagai pembangun sektor ekonomi. Industri 4.0 mengacu pada konsep penggunaan internet of things, serta smart and cloud based manufacturing. Perubahan revolusi industri dihadapi dengan adanya Making Indonesia 4.0 dengan salah satu prioritasnya pemberdayaan UMKM.  Kendala pelaku UMKM dari permodalan, keterampilan manajerial, hingga penggunaan teknologi, sehingga diperlukan sebuah kesiapan UMKM dalam menghadapi Industri 4.0. Pada penelitian ini, Kesiapan UMKM mengacu pada konsep e-readiness untuk mengetahui kesiapan dalam mengadopsi, menggunakan dan memanfaatkan teknologi informasi. Tujuan penelitian berupa pengembangan model untuk mengidentifikasi kesiapan UMKM Kab. Karawang terhadap revolusi industri 4.0 Metode penelitian berupa penelitian deskriptif untuk mengembangkan model penelitian dalam mengidentifikasi kesiapan UMKM pada era revolusi industri 4.0, dengan metode random sampling dari 100 responden. Hasil Penelitian berupa pengembangan model penelitian dengan hasil survey yang menyatakan banyaknya pelaku UMKM berusia muda mampu beradaptasi dan menangkap peluang perkembangan masa kini dan permintaan pasar, namun tidak mengikuti komunitas UMKM menjadi perhatian khusus sehingga diperlukan upaya pendekatan lebih lanjut dalam mengembangkan industri UMKM di Kabupaten Karawang, agar dapat dilakukan pembinaan.Kata kunci— Kesiapan UMKM; Industri 4.0; e-readiness